CURRENT PROBLEMS OF TAX ADMINISTRATION IN RUSSIA - P. A. Kozlov; M. V. Kashirina (Финансы: теория и практика)
The article considers the problems arising in the course of tax administration. The article studies them with purpose to introduce relevant amendments to the law in the future, as the current tax administration mechanism does not fully meet the criteria of efficiency and the expectations of authorities. It isevident that there are obvious flaws in the existing mechanism of tax administration and they hinder a proper filling of the budget and hamper ensuring the social protection especially needed under crisis conditions. The authors considers the most important problems, i.e. the enforcement mechanism for tax payment, collection of tax arrears, fly-by-night companies, the non-indexing of some economic indicators for tax purposes, insufficient tax deductions, difficulties in the exchange of information between tax and other government bodies, some provisions of legal acts and different authors’ views related to the research topic. Amendments to tax law provisions would update the Russian tax system and result in more efficient filling of the budget and higher life quality in Russia.